2014
DOI: 10.1016/j.jim.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heavy and light chain sequences of conventional camelid antibodies from Camelus dromedarius and Camelus bactrianus species

Abstract: Camel antibodies have been widely investigated, but work has focused upon the unique heavy chain antibodies found across camelid species. These are homodimers, devoid of light chains and the first constant heavy chain domain. Camelid species also display conventional hetero-tetrameric antibodies with identical pairs of heavy and light chains; in Camelus dromedarius these constitute 25% of circulating antibodies. Few investigations have been made on this subset of antibodies and complete conventional camel IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…inhibition is mediated by the extended CDR-H3s coding for the convex-shaped paratopes that penetrate into the enzyme catalytic cleft (23,26). Consistent with the studies by others (30), our in-depth analysis of over 950 individual camelid antibodies available from the international ImMunoGeneTics (IMGT), Kabat, and abYsis databases determined that there is a bimodal distribution in their CDR-H3 length with peaks at 12 and 19 residues (Fig. S2A).…”
Section: Significancesupporting
confidence: 87%
“…inhibition is mediated by the extended CDR-H3s coding for the convex-shaped paratopes that penetrate into the enzyme catalytic cleft (23,26). Consistent with the studies by others (30), our in-depth analysis of over 950 individual camelid antibodies available from the international ImMunoGeneTics (IMGT), Kabat, and abYsis databases determined that there is a bimodal distribution in their CDR-H3 length with peaks at 12 and 19 residues (Fig. S2A).…”
Section: Significancesupporting
confidence: 87%
“…Surprisingly, these turned out to have CDR1 and CDR2 canonical structure combinations identical to those of the corresponding human germline orthologs. In addition and in agreement with previous analysis, 20,21 we identified an IGHV5 and IGHV7 gene family, adding to the existing knowledge of IGHV genes in camelids. Using X-ray crystallography we confirmed the presence of predicted canonical structures similar to human canonical folds on 2 selected camelid antibodies separately directed against the therapeutic targets CD70 and MET.…”
Section: Introductionsupporting
confidence: 90%
“…With hindsight, the notion that sdAbs might preferentially target particular types of antigenic structures may not seem totally unexpected, given their recombination from distinct repertoires of V, D and J genes (see Box 1 ), 8 their potential ontogeny from separate B-cell precursors, 9 and for camelid V H Hs, their specialized constant regions bearing very long hinge regions. 10 However, the specific mechanisms of sdAb antigen recognition ( e.g ., the tertiary structures and physicochemical properties of sdAb:antigen interfaces, which may differ fundamentally from those of conventional antibody:antigen interfaces) remain unclear, although several studies have suggested protein cleft recognition as a general function for both V H Hs 11 and V NAR s. 12 Over time, the idea that sdAbs can target ‘cryptic’ epitopes (so-called because they are inaccessible to conventional antibodies, either for steric reasons or due to their fundamental antigenic properties) has become entrenched, and although several case studies have supported it, its generality and implications are questionable. Several excellent recent reviews and opinion pieces have alluded to the nature of sdAb paratopes and their interactions with antigens, but have either not been rigorous in their approach or have incompletely addressed the topic, analyzing the properties of sdAb paratopes only, with no comparison to those of conventional antibodies.…”
Section: Introductionmentioning
confidence: 99%